Coupled Temporal Fluctuation and Global Signal Synchronization of Spontaneous Brain Activity in Hypnosis for Respiration Control: An fMRI Study. (1st March 2020) - Liu, Yanjun; He, Yini; Li, Rongmao; Yu, Shaode; Xu, Jianyang; Xie, Yaoqin
Graphical abstract: Highlights: Hypnosis was observed with increased brain activity in calcarine cortex, fusiform gyrus and middle temporal gyrus. Hypnosis was observed with decreased brain activity in posterior cerebellum. Enhanced positive correlations between temporal fluctuation and signal synchronization were observed during hypnosis. Coupled correlation between temporal fluctuation and global signal synchronization was observed during hypnosis. Abstract: Hypnosis is a psychological technology proved to be effective in respiratory motion control, which is essential to reduce radiation dose during radiotherapy. This study explored the neural mechanisms and cognitive neuroscience of hypnosis for respiration control by functional magnetic resonance imaging with a within-subject design of 15 healthy volunteers in rest state (RS) and hypnosis state (HS). Temporal fluctuation and signal synchronization of brain activity were employed to investigate the altered physiological performance in hypnosis. The altered correlations between temporal fluctuation and signal synchronization were examined within large scale of intrinsic networks which were identified by seed-wise functional connectivity. As a result, hypnosis was observed with increased activity in the right calcarine, bilateral fusiform gyrus and left middle temporal gyrus, and with decreased activity in the left cerebellum posterior lobe (inferior semilunar lobule part). Compared to RS, enhanced positive correlations were observed between temporal fluctuation and signal synchronization in HS. Most importantly, coupled correlation was observed between temporal fluctuation and global signal synchronization within the identified intrinsic networks ( R = 0.3843, p > 0.05 in RS; R = 0.6212, p < 0.005 in HS). The findings provide implications for the neural basis of hypnosis for respiratory motion control and suggest the involvement of emotional processing and regulation of perceptual consciousness in hypnosis.